2018
DOI: 10.5152/tjg.2018.17431
|View full text |Cite
|
Sign up to set email alerts
|

Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In this context, the frequency of acute HAV infection in our area is consistent with the studies from Turkey. Similar to our study, Karacaer et al reported that the incidence of acute HAV infection was higher especially in adolescence in which included 17 centers' data for the epidemiology of acute viral hepatitis (34). Çeviker et al determined that complications due to acute hepatitis A were observed more frequently in adult ages (35).…”
Section: Discussionsupporting
confidence: 87%
“…In this context, the frequency of acute HAV infection in our area is consistent with the studies from Turkey. Similar to our study, Karacaer et al reported that the incidence of acute HAV infection was higher especially in adolescence in which included 17 centers' data for the epidemiology of acute viral hepatitis (34). Çeviker et al determined that complications due to acute hepatitis A were observed more frequently in adult ages (35).…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of acute HB below 1/100,000 recorded in 2016 represents the lowest value since the mandatory notification of acute HB was introduced in APV [10]. A similar trend of acute HB incidence rates was registered in Serbia (1.77/100,000) and, to a three-fold lower extent, in the European Union (≈0.6/100,000) [41][42][43][44]. Compared to acute HB, the incidence of chronic HB in APV was several times higher (3.7/100,000 in 2017) [10], which can be considered as a reflection of the unfavorable epidemiological situation and the lack of universal HB vaccination in the past.…”
Section: Discussionmentioning
confidence: 75%
“…In a very interesting multicenter study conducted in Turkey, Karacaer et al (1) reported on changes in acute viral hepatitis epidemiology in the adult population. The most commonly found microorganisms were hepatitis B virus (55.2%) and hepatitis A virus (HAV) (37.6%), and types of acute viral hepatitis significantly differed according to the age group.…”
Section: Dear Editormentioning
confidence: 99%